Automatic screening of antioxidants based on the evaluation of kinetics of suppression of chemiluminescence in a luminol–hydrogen peroxide system using a sequential injection analysis setup with a flow-batch detection cell. Issue 19 (26th April 2019) - Chládková, Gabriela; Kunovská, Klára; Chocholouš, Petr; Polášek, Miroslav; Sklenářová, Hana
Abstract : Real time monitoring of kinetic profiles of antioxidant activity of phenolic substances. Abstract : A sequential injection analysis system with sensitive chemiluminescence detection using a flow-batch detection cell was developed for the real time monitoring of kinetic profiles of antioxidant activity of phenolic substances in a luminol–Fe(iii )–hydrogen peroxide system during a 60 s stop–flow period. Selected substances including coumaric acid, caffeic acid, hesperidin, ascorbic acid, resveratrol, rutin, chlorogenic acid, quercitrin, epicatechin, phloridzin, phloretin, and Trolox as a reference standard were tested with respect to different chemiluminescence signal kinetics. The evaluation of antioxidant activity was expressed as the quenching efficacy index Q . Our method has a wide working concentration range of 4–250 μmol L −1 for Trolox antioxidant activity. The real time kinetic profiles based on the chemiluminescence quenching half-life of both quick and slow antioxidants were also determined. A sample throughput of 30 h −1 was demonstrated. The antioxidant activity of apple and black elder fruit extracts was evaluated.